Archaeology and Celtic Myth: Some Points of Comparison and Convergence - Wooding, Jonathan M. (Temenos, 2019)
This article arises from a plenary invitation to compare myth and archaeology in the context of Celtic-speaking cultures. Approaches to myth in this context have undergone significant reassessment in the light of revisionist approaches to definitions of native' culture and Celtic' identity. These reassessments have implications for comparisons that are made between archaeological evidence and narratives, or elements thereof, that are arguably identifiable as mythic. New approaches to data in both subject areas affect roles that have long been played by myth in public reception of archaeological discoveries and in supporting cultural identities. Past approaches to such comparisons inspire caution, even scepticism, but some critical use of myth as an idea can be seen as productive - for example, in questioning conservative interpretations of textual or material data.